Health-Promoting Role of Lactiplantibacillus plantarum Isolated from Fermented Foods - Natalia Garcia-Gonzalez; Natalia Battista; Roberta Prete; Aldo Corsetti (Microorganisms, 2021)
Fermentation processes have been used for centuries for food production and preservation. Besides the contribution of fermentation to food quality, recently, scientific interest in the beneficial nature of fermented foods as a reservoir of probiotic candidates is increasing. Fermented food microbes are gaining attention for their health-promoting potential and for being genetically related to human probiotic bacteria. Among them, Lactiplantibacillus (Lpb.) plantarum strains, with a long history in the food industry as starter cultures in the production of a wide variety of fermented foods, are being investigated for their beneficial properties which are similar to those of probiotic strains, and they are also applied in clinical interventions. Food-associated Lpb. plantarum showed a good adaptation and adhesion ability in the gastro-intestinal tract and the potential to affect host health through various beneficial activities, e.g., antimicrobial, antioxidative, antigenotoxic, anti-inflammatory and immunomodulatory, in several in vitro and in vivo studies. This review provides an overview of fermented-associated Lpb. plantarum health benefits with evidence from clinical studies. Probiotic criteria that fermented-associated microbes need to fulfil are also reported.